IMPLEMENTASI CLOUD BASED VIDEO CONFERENCE SYSTEM MENGGUNAKAN JITSI - Dewi Laksmiati (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
Nowadays communication and information plays an important role. So that distance and time must be simplified so that decisions are made easily. Video conference is one. One result of the technological advancements that facilitate human is the Video conference. Video conference is an interactive communication device that can be used by second parties and can be used further through two-way audio and video delivery. Video conference technology must be in accordance with the International Telecommunication Union Standardization so that this communication is as desired, while H323 is the ITU standard for Video conference technology that includes audio, video and data related to networks that are not in accordance with Service Quality (QoS)